Just world beliefs and forgiveness: The mediating role of implicit theories of relationships. (July 2016) - Bartholomaeus, Jonathan; Strelan, Peter
Abstract: The belief in a just world (BJW) influences how people navigate their relationships. BJW effects differ depending on the extent to which one's BJW is concerned with the self (BJW-self) and others (BJW-other). In this study ( N  = 160) we replicated previous research showing that BJW-self encourages forgiveness operationalized as benevolence and extended it to show, for the first time, that BJW-self predicts decisional forgiveness but, unexpectedly, not emotional forgiveness. Conversely, BJW-other encourages negative responding. Most importantly, the study makes a new contribution to BJW theorizing by integrating principles from implicit theories of relationships. Mediation models indicated that BJW-self obtains its association with forgiveness through growth beliefs, whereas BJW-other is associated with negative responding via the agency of destiny beliefs. Highlights: Integrates implicit theories of relationships into the BJW framework First study to measure decisional and emotional forgiveness in relation to BJW Demonstrates that BJW-self predicts forgiveness indirectly through growth beliefs BJW-other predicts negative responding indirectly through destiny beliefs.